Al-Qur’an dan Pembahasalokalan di Indonesia - Rohmana, Jajang A (Lajnah Pentashihan Mushaf Al-Qur'an, 2021)
This paper aims to explain the use of term I am (aing) in Sundanese Qur’anic exegesis or tafsīr. The object of this study is the use of the word “Aing” (I am) in the Qur’anul Adhimi of Haji Hasan Mustapa (1852-1930) and some other Quranic exegesis works of K.H. Ahmad Sanusi (1888-1950). Both Hasan Mustafa and Ahmad Sanusi use the term “Aing” (I am) as a pronoun for the first person singular. It is through the library research method and sociolinguistic approach this study shows that the use of the term “Aing” is not only related to the theological belief of the superiority of Allah the Almighty to be compared with the creation but also a reflection of the impact of social stratification in the society that puts the term “Aing” (I am) in the highest level of language. Although now the term aing is considered to be impolite, but the use of the term is still acceptable because it is considered to be able to accommodate more the superiority of God than other terms of the low social stratification. It is a consciousness of the diglossic language in the Qur’anic exegesis as a reflection of the Sundanese ethics of the attitude of man toward God into the highest level of language which is different from other situation.